Role of Coronary Calcium Score as a Screening Tool for Excluding Significant Coronary Artery Disease in High Risk Asymptomatic Patients - Muhammad Imran Khan; Zenab; Fariha Afzal (Gandhara University, 2022)
OBJECTIVES: To determine correlation of zero coronary artery calcium score (CACS) with non-significant coronary artery stenosis by using computed tomography coronary angiography (CTCA). METHODOLOGY: 62 patients with suspected coronary artery disease (CAD) underwent CACS test and CTCA from April 2018 to November 2020. Patients were examined with 160 slice multidetector CT and grouped according to their age, gender, CACS, and maximum coronary luminal stenosis. CACS was assessed using Agatston scoring and degree of stenosis was assessed by automatic software and severity was scored according to CAD-RADS. The correlation between these two main variables was calculated using Spearman rank correlation. RESULTS: The 62 patients were divided into four groups according to CACS, using the Agatston Unit (AU). Group 1; 0 AU (41 patients, 66.13%), Group 2; 1-100 AU (13 patients, 20.97%) Group 3; 101-400 AU (4 patients, 6.45%), Group 4; 401-1000 AU (4 patients, 6.45%). In 41 patients with zero calcium score (32 males and 9 females), 38 patients (92.68%) were found to have no coronary artery stenosis, 2 patients (4.87%) had mild coronary artery stenosis and 1 patient (2.43%) had moderate coronary artery stenosis. Total 35 patients presented for screening purpose out of which 25 (71%) had zero calcium score and no significant coronary artery disease. CONCLUSION: In high risk patients, zero calcium score excludes significant coronary artery stenosis (50%), hence coronary calcium score is a good screening tool before subjecting patients to coronary angiography.